The Relationships Between Lipid Accumulation Product Levels and Cognitive Decline Over 4 Years in a Rural Area of Xi’an, China - Wang, Yanyu; Wei, Shan; Zhou, Rong; Shang, Suhang; Dang, Liangjun; Gao, Ling; Chen, Chen; Huo, Kang; Wang, Jingyi; Wang, Jin; Qu, Qiumin (Frontiers in Aging Neuroscience, 2021)
Abstract Background and Aims: The relationships between blood lipid levels and obesity and cognitive impairment have not been fully determined. Considering that the lipid accumulation product (LAP) is a composite index of blood lipid levels and obesity, we investigated the relationships between LAP levels at baseline and cognitive decline over 4 years. Methods: A total of 983 subjects (≥ 40 years) from a longitudinal cohort in a village of Xi'an, China, who completed the baseline survey were followed-up for 4 years. All participants underwent face-to-face interviews and cognitive assessments at baseline and at the 4-year follow-up. The Mini-Mental State Examination (MMSE) was used to assess cognitive function, and an MMSE score dropping ≥2 points from baseline was defined as cognitive decline. The relationships between LAP and cognitive decline were analyzed by linear regression models. Results: During the 4-year follow-up, 172 patients exhibited cognitive decline (17.5%). Univariate analysis showed that the rate of change in MMSE score was significantly different between the low-LAP group and the high-LAP group (t=-2.26, p=0.024). Multiple linear regression indicated that a high LAP was positively associated with cognitive decline (β=0.564, p=0.012). Stratified multivariate analysis showed that LAP was positively associated with cognitive decline in the normal blood pressure female subgroup (β=1.29, p=0.002) but not in the high blood pressure group or the male group. Conclusions: High LAP is associated with cognitive decline in females with normal blood pressure but not in those with high blood pressure or males. This indicates that the relationships between blood lipid levels and obesity and cognitive impairment may be affected by blood pressure and sex.